Systematic position and conservation aspects of Melinaea mnasias thera (Lepidoptera: Nymphalidae: Danainae) - Augusto H. B. Rosa; Eduardo P. Barbosa; Niklas Wahlberg; André V.L. Freitas (Nature Conservation Research: Заповедная наука, 2024)
The tribe Ithomiini (Nymphalidae: Danainae) includes nearly 400 species of butterflies distributed from Mexico to Northern Argentina, and adults of all species are aposematic and the main models in several Neotropical mimicry rings. The subtribe Melinaeina, a small group composed of five genera of large ithomiines, is the sister group of all remaining groups in the tribe Ithomiini. With 14 recognised species, the genus Melinaea is the most species rich, and also the most widespread within the Melinaeina. From all species of the genus, Melinaea mnasias is considered very rare and a little known one. This is also true for Melinaea mnasias thera, a subspecies from the Atlantic Forest with less than 20 specimens known in all world museums. Studies combining systematics, ecology, biogeography and natural history are priority in tropical areas, especially when focusing on threatened species. Thus, the aim of this study was to compile all available knowledge on the threatened M. mnasias thera, providing information to future management plans focusing on the conservation of this butterfly and its habitats. Data were compiled from scientific collections and personal observations, and the systematics of species of Melinaea was assessed by DNA sampling and analysis. The obtained phylogeny recovered the subtribe Melinaeina organised in two clades, the first composed by Olyras + Paititia and the second by Eutresis + (Athyrtis + Melinaea). Melinaea mnasias thera was recovered as a sister to M. mnasias lucifer. A total of only 17 specimens of M. mnasias thera from four Brazilian localities were found in all revised collections. However, well-preserved forests are present only at one of these localities, in the southern Bahia state, from where a recent specimen has been collected, suggesting that the last populations of M. mnasias thera are restricted to this region. If this is true, the real conservation status of this species could be much more critical than the estimated.